The association of 25-hydroxyvitamin D3 and D2 with behavioural problems in childhood. - Anna-Maija Tolppanen; Adrian Sayers; William D Fraser; Glyn Lewis; Stanley Zammit; Debbie A Lawlor (PLoS ONE)
Background Higher serum concentrations of 25-hydroxyvitamin D (25(OH)D), an indicator of vitamin D synthesis and intake, have been associated with better mental health and cognitive function. Concentrations of 1,25-dihydroxyvitamin D(3) (the active vitamin D(3) metabolite) have been associated with openness and extrovert behaviour, but 25(OH)D concentrations have not been associated with behavioural problems in humans. Methods We investigated the prospective association between the different forms of 25(OH)D - 25(OH)D(3) and 25(OH)D(2)- and childhood behavioural problems in Avon Longitudinal Study of Parents and Children (ALSPAC). Serum 25(OH)D(3) and 25(OH)D(2) concentrations were assessed at mean age 9.9 years. Incident behavioural problems were assessed with Strengths and Difficulties Questionnaire (SDQ; emotional symptoms, conduct problems, hyperactivity-inattention problems, peer relationship problems and pro-social behaviour subscales and total difficulties score) at mean age 11.7. Sample sizes varied between 2413-2666 depending on the outcome. Results Higher 25(OH)D(3) concentrations were weakly associated with lower risk of prosocial problems (fully adjusted odds ratio: OR (95% confidence interval: CI) 0.85 (0.74, 0.98)). Serum 25(OH)D(3) or 25(OH)D(2) concentrations were not associated with other subscales of SDQ or total difficulties score after adjusting for concfounders and other measured analytes related to vitamin D. Conclusions Our findings do not support the hypothesis that 25-hydroxyvitamin D status in childhood has important influences on behavioural traits in humans.